Liquid Phase Peptide Synthesis via One‐Pot Nanostar Sieving (PEPSTAR). (24th February 2021) - Yeo, Jet; Peeva, Ludmila; Chung, Seoyeon; Gaffney, Piers; Kim, Daeok; Luciani, Carla; Tsukanov, Sergey; Seibert, Kevin; Kopach, Michael; Albericio, Fernando; Livingston, Andrew
Abstract: Herein, a one‐pot liquid phase peptide synthesis featuring iterative addition of amino acids to a "nanostar" support, with organic solvent nanofiltration (OSN) for isolation of the growing peptide after each synthesis cycle is reported. A cycle consists of coupling, Fmoc removal, then sieving out of the reaction by‐products via nanofiltration in a reactor‐separator, or synthesizer apparatus where no phase or material transfers are required between cycles. The three‐armed and monodisperse nanostar facilitates both efficient nanofiltration and real‐time reaction monitoring of each process cycle. This enabled the synthesis of peptides more efficiently while retaining the full benefits of liquid phase synthesis. PEPSTAR was validated initially with the synthesis of enkephalin‐like model penta‐ and decapeptides, then octreotate amide and finally octreotate. The crude purities compared favorably to vendor produced samples from solid phase synthesis. Abstract : PEPSTAR, a „rising star" in peptide synthesis, features a „nanostar" support to grow peptides with organic solvent nanofiltration for isolation. The three‐armed and monodisperse nanostar enables efficient nanofiltration and real‐time reaction monitoring. A cycle consists of coupling, Fmoc removal and nanofiltration, which all performed continuously in a synthesizer to produce high purity peptide crudes through a one‐pot approach.